2018
DOI: 10.1136/bjophthalmol-2018-312724
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in genetically modified animal models of glaucoma and their roles in drug repositioning

Abstract: Glaucoma is one of the leading causes of vision loss in the world. Currently, pharmacological intervention for glaucoma therapy is limited to eye drops that reduce intraocular pressure (IOP). Recent studies have shown that various factors as well as IOP are involved in the pathogenesis of glaucoma, especially in the subtype of normal tension glaucoma. To date, various animal models of glaucoma have been established, including glutamate/aspartate transporter knockout (KO) mice, excitatory amino acid carrier 1 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 97 publications
1
35
0
Order By: Relevance
“…These results suggested that aRGCs and ipRGCs have high tolerance to IOP-independent pathogenic factors that may be involved in the progress of glaucoma. 32 We showed that aRGCs and ipRGCs are tolerant to glutamate neurotoxicity. Our findings are supported by a recent study demonstrating that susceptibility of different types of genetically identified RGCs to NMDA excitotoxicity varies significantly, and that aRGCs are the most resistant RGCs to NMDA excitotoxicity.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These results suggested that aRGCs and ipRGCs have high tolerance to IOP-independent pathogenic factors that may be involved in the progress of glaucoma. 32 We showed that aRGCs and ipRGCs are tolerant to glutamate neurotoxicity. Our findings are supported by a recent study demonstrating that susceptibility of different types of genetically identified RGCs to NMDA excitotoxicity varies significantly, and that aRGCs are the most resistant RGCs to NMDA excitotoxicity.…”
Section: Discussionmentioning
confidence: 92%
“…[29][30][31] Retinal degeneration in GLAST knockout (KO) mice may occur due to various factors, such as aging, glutamate neurotoxicity, and oxidative stress, which are important risk factors in human glaucoma. 32 Previous studies have reported that glaucoma patients show downregulation of glutamate transporters and glutathione levels, 33,34 suggesting that GLAST KO mice are useful as animal models of NTG.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Animal models provide valuable information about the diagnosis and course of disease. They also enable the development of new therapeutic approaches and allow for the monitoring of effects of the therapy (Harada et al, 2019). The DBA/2J mice strain is commonly used as an animal model that mimics many aspects of congenital human glaucoma, particularly pigmentary glaucoma (PG).…”
Section: Discussionmentioning
confidence: 99%
“…Several issues contributing to the lack of success of drugs in clinical trials could be suggested, but in the case of glaucoma, the lack of an animal model that fully mimics the human disease is an important factor that adds to this failure [331]. Another issue is that, in preclinical trials, several studies use a preventive strategy to assess the effect of a specific drug, as opposed to the human condition in which the treatment starts after diagnosis.…”
Section: Potential Pitfalls In Translating Preclinical Studies Into Tmentioning
confidence: 99%